Implementing Interactive Games to Enhance English Grammar and Vocabulary in Writing Skills - Quiroz Alonzo, Bianca Gabriela; Jiménez Álvarez, Marisela; Bonilla Tenesaca, Josué Reinaldo (Arandu UTIC, 2026)
The effective acquisition of English as a foreign language (EFL) remains a persistent challenge in Ecuadorian public education, particularly in the development of writing skills. Although curricular reforms aim to foster communicative competence, many secondary students continue to struggle with the foundational components of grammar and vocabulary—key elements for coherent and accurate written expression. These difficulties are often intensified by students' perception of grammar as tedious and vocabulary as easily forgettable, leading to low motivation and weak language retention. Considering the growing importance of English proficiency for academic and professional opportunities, this study explores the potential of interactive games as a pedagogical tool to enhance grammar and vocabulary learning in writing tasks. Drawing on game-based learning principles, which emphasize engagement, motivation, and meaningful language use, the research evaluates the effectiveness of integrating interactive grammar and vocabulary games in a tenth-grade EFL classroom. Using a mixed-methods design, the study combines pre- and post-tests with interviews and classroom observations to measure changes in students’ motivation, engagement, and writing performance. The results are expected to demonstrate that interactive games can significantly support language retention and improve grammatical accuracy and vocabulary use in written communication, offering a dynamic alternative to traditional teaching practices.